(untitled) (Research, Society and Development, 2022)
Objective: to carry out a scope review protocol to map scientific evidence on effective communication strategies for the continuity of safe care for pediatric patients in interdisciplinary intensive care. Method: The protocol used the method proposed by the Joanna Briggs Institute, Reviewers Manual 2020, which establishes the five phases: 1) identification of the research question; 2) identification of relevant studies; 3) study selection; 4) data mapping; and 5) grouping, summarizing and reporting the results. To prepare the review synthesis, the recommendations of the PRISMA-ScR checklist (PRISMA extension for Scoping Reviews) will be followed. Studies will be selected independently by two researchers. For the interpretation of the results, the IRaMuTeQ software will be used. Then, analysis of the frequency of the words and the connection between them, that is, word cloud and similarity analysis. The expectation of this study is to identify scientific evidence that can support the research question and collaborate for a reflective analysis on the subject.